SOEP-RV: Linking German Socio-Economic Panel data to pension records - Holger Lüthen; Carsten Schröder; Markus M. Grabka; Jan Goebel; Tatjana Mika; Daniel Brüggmann; Sebastian Ellert; Hannah Penz (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The aim of the project SOEP-RV is to link data from participants in the German Socio-Economic Panel (SOEP) survey to their individual Deutsche Rentenversicherung (German Pension Insurance) records. For all SOEP respondents who give explicit consent to record linkage, SOEP-RV creates a linked dataset that combines the comprehensive multi-topic SOEP data with detailed cross-sectional and longitudinal data on social security pension records covering the individual's entire insurance history. This article provides an overview of the record linkage project, highlights potentials for analysis of the linked data, compares key SOEP and pension insurance variables, and suggests a re-weighting procedure that corrects for selectivity. It concludes with details on the process of obtaining the data for scientific use.
Keywords: C89; C18; 330; record linkage; SOEP; SOEP-RV; pension records; consent